Writer identification based on the arc pattern transformation - Yoshimura, I.; Yoshimura, M. (Pattern Recognition, 9th International Conference on, 1988: Proceedings, 2003)
A method of writer identification for handwritten characters that is based on a series of arc-pattern transformations, defined as transformations from character patterns to frequency patterns of arcs with given chords and curvatures, is proposed. The method is an extension of that due to K. Shakunaga et al. (1984). Its effectiveness is examined experimentally using copies of a Japanese sentence with 25 letters, written by hand by each of 24 persons. About 2% average increase in correct identification rate is achieved by this method compared with the method of Shakunaga et al.< >